Effects of Power-Oriented Resistance Training During an Altitude Camp on Strength and Technical Performance of Elite Judokas - Almeida, Filipa; Padial, Paulino; Bonitch-Góngora, Juan; de la Fuente, Blanca; Schoenfeld, Brad J.; Morales-Artacho, Antonio J.; Benavente, Cristina; Feriche, Belén (Frontiers in Physiology, 2021)
This study investigated the effect of a 3-week power-oriented resistance training program performed at moderate altitude on leg power output variables in a countermovement jump, a related judo technique (ippon-seoi-nage) and the relationship between them. Twenty-four elite male judokas were randomly assigned to a hypobaric hypoxia or normoxia group. Mechanical outputs from an incremental loaded countermovement jump test and the kinematic variables transferred to a dummy during an ippon-seoi-nage test (time to execution and movement accelerations) were assessed before, after, one and two weeks after training. Results indicated an increase in explosive leg capacity both at moderate altitude (2320 m asl) and sea level. The hypoxia group showed additional benefits when compared to normoxia group for peak velocities with different percentages of the body weight, maximal theoretical velocity and jump height after the training period, and these additional benefits in jump height were maintained two weeks after training. The hypoxia group achieved a higher peak performance in peak velocity and jump height than normoxia group (peak velocity: 8.8% vs. 5.6%, jump height: 8.2% vs. 1.4%, respectively) and was achieved earlier in hypoxia (after training) than in normoxia (one week after training). However, there was a detrimental effect for the hypoxia group on the times of execution and acceleration of the ippon-seoi-nage compared to the normoxia group. These results suggest that altitude training may induce faster and greater improvements in explosive leg extension capacity. Specific technique-oriented training should be included at altitude to prevent technique impairment.